Adiabatic relaxation energy (ARE) for KL states of atoms - Soni, S. N. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
A method has been presented for calculating semiempirically the adiabatic relaxation energy (ARE) for excited states of atoms which are ionised in K- and L-shells simultaneously. The validity of the method has been tested by calculating the complete Kα3α4 satellite spectrum of nickel, which is found to be in excellent agreement with the observed spectrum. Finally, the values of ARE for KL states of atoms with Z =12 to 44 have been presented.